Femtocell network : challenges and future trends - Saeed, Rashid Abdelhaleem (IIUM Press, 2011)
Currently, Femtocell technology emerged for cellular wireless networks, which has rapidly engrossed cellular industry. The principle of femtocell to mobile operators is to reduce the network operation cost and increase indoor coverage which is also considered a possible path to the fixed-mobile convergence (FMC) goal. Femtocell access point (FAP) or home base station (HBS) is a base station designed for use in user premises (home or small business). It intends to serve small number of users i.e. 4 users and covers about 30 meter square similar to existing WiFi access points. The uniqueness of femtocell in contrast with micro and macrocellular it connects to cellular network through broadband network i.e. xDSL. The motivation of femtocell is to improve signal quality in indoor environments and provide high speed wireless access mobile-Internet users. However, femtocell introduces new challenges to the mobile operators (MOs) in terms of handoff between femto and macrocells, interference management, localization and synchronization, security and network management. Accordingly, the objective of this chapter is to studies the challenges and future trends for femtocell communication, and summarize by explored some open issues as well